CCR7A defines a subpopulation of IgD+IgM- B cells with higher IgD secreting capacity in the rainbow trout skin - Morel, Esther; Herranz-Jusdado, Juan German; Simón, Rocío; Vicente-Gil, Samuel; González, Lucía; Tafalla, Carolina (Frontiers in Immunology, 2025)
B cells exclusively expressing IgD on the cell surface (IgD+IgM− B cells) have been identified in mammals, where they seem to play a still not well-defined role in peripheral tolerance. These cells have also been reported in catfish (Ictalurus punctatus) peripheral blood and in several mucosal tissues of rainbow trout (Oncorhynchus mykiss), including gut, gills and skin. As in mammals, the precise function of these cells remains obscure, yet, in rainbow trout mucosal surfaces, these cells have been shown to be differentiated to plasma-like cells. Interestingly, in the gills, these IgD+IgM− B cells expressed high levels of the CC chemokine receptor 7 (CCR7), receptor that in mammals controls the migration of B and T cells to secondary lymphoid organs. In this work, we have established that this is also true for the trout skin, where CCR7 defines a specific subset of IgD+IgM− B cells that are further differentiated to a plasma-like profile than those not expressing CCR7. These findings increase the current understanding of this enigmatic B cell population and point to CCR7 as a key differentiation marker for these cells.